Analisis Atas Pengakuan Pendapatan Dan Beban Pada Industri Gondorukem Perum Perhutani Unit III Dan Kesesuaiannya Dengan Psak 32 - Sutarti, Sutarti (STIE Kesatuan, 2010)
Perum Perhutani represents one of State Owned Corporates (BUMN) thatâs given authority as a single organizer of forsts in Indonesia, especially in Java Island which is divided into three sectors, those are Perum Perhutani Unit I in Central Java, Perum Perhutani Unit II in East Java, and Perum Perhutani Unit III in West Java & Banten. The central office is located in Jakarta. Gondorukem Industry represents a division of Autonomous Business Unit of Perum perhutani. The purpose of this research is to analize revenues and expenses of Forestry Company, especially in Gongorukem industry of Perum Perhutani Unit III. Since Indonesia Accountants Association (IAI) has arranged Finance Standard Accounting Statement (PSAK) 32,hence for their finance statement standard all of Forestry Companies have to refer to Finance Standard Accounting Statement 32. The analysis performed is to know whether revenues and expenses admission in Gondorukem Industry of Perum Perhutani Unit III have met revenues and expenses admission at PSAK 32 concerning forestry accounting. Based on the result of the research carried out by the writer in Gondorukem Industry of Perum Perhutani Unit III, itâs obtained that revenues and expenses recognition in Gondorukem Industry of Perum Perhutani Unit III used accrual basic. It means that itâs in accordance with PSAK 32 which state that the revenues and expenses have to be recognized by using accual basic.